Kecenderungan Global Pendidikan Tinggi dan Pergeseran Paradigma Reformasi Pendididikan Tinggi pada Institusi Pendidikan Tinggi Keagamaan Islam - Ahmad Syamsul Arifin (Universitas Alma Ata, 2015)
Abstract Massifikation impact of globalization and the phenomenon has changed the global trend of higher education around the world over the past decades. The global trend include: globalization and internaionalisasi, access and equity, private higher education and privatization, quality assurance framework, accountability and qualifications, financing higher education, centralization and crisis of academic profession, experience of students, teaching, learning and assessment, information technology communication and distance education, research, university-industry linkages. The global trend is also creating a number of opportunities and challenges for institutions of higher education. More juah, the global trend is also helped provide a significant impact to the paradigm shift in institutional reform of higher education, including higher education which includes the Islamic religious dimension of globalization, localization, and individualization. Keywords: global trends, Higher Education, Higher Education Islamic Religious